The profile of presidente in the sports organizations of the Azores autônomos region - André Soares; Mário Coelho Teixeira (Universidade Salgado de Oliveira, 2020)
The following study has the main objective, of characterizing the functional profile of competences of the Presidents of Sports Organizations of the Autonomous Region of the Azores. Data were collected through a questionnaire to the presidents of sports organizations, organized into two groups: profile of the president and tasks/activities of the president. Forty-six presidents of sports organizations participated in the study (n=46). The most valued function was coordination and direction. We find significant differences in the training and time they hold in the position of presidents.